The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/5879723
|View full text |Cite
|
Sign up to set email alerts
|

Proton versus Photon Radiotherapy for Pediatric Central Nervous System Malignancies: A Systematic Review and Meta-Analysis of Dosimetric Comparison Studies

Abstract: Background Radiotherapy (RT) plays a fundamental role in the treatment of pediatric central nervous system (CNS) malignancies, but its late sequelae are still a challenging question. Despite developments in modern high-conformal photon techniques and proton beam therapy (PBT) are improving the normal tissues dose-sparing while maintaining satisfactory target coverage, clinical advantages supporting the optimal treatment strategy have to be better evaluated in long-term clinical studies and assessed in further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 45 publications
(103 reference statements)
0
16
1
2
Order By: Relevance
“…Proton radiation therapy has been used for cancer treatment since the 1960s, but until recently its use was limited by the number of available facilities 5 . Proton radiotherapy can decrease toxicity by reducing radiation exposure of healthy brain tissue, while delivering equivalent anti-tumor efficacy compared with X-ray radiotherapy 6,7 . In that regard, a recent pivotal study in children with medulloblastoma identified superior intellectual outcomes in patients treated with proton compared with photon radiotherapy 8 .…”
mentioning
confidence: 99%
“…Proton radiation therapy has been used for cancer treatment since the 1960s, but until recently its use was limited by the number of available facilities 5 . Proton radiotherapy can decrease toxicity by reducing radiation exposure of healthy brain tissue, while delivering equivalent anti-tumor efficacy compared with X-ray radiotherapy 6,7 . In that regard, a recent pivotal study in children with medulloblastoma identified superior intellectual outcomes in patients treated with proton compared with photon radiotherapy 8 .…”
mentioning
confidence: 99%
“…One 15-year-old girl with an intracranial germinoma received whole ventricular irradiation (WVI).On analysis of the technique of PBT planning, MFO was used in 21 patients (of which 17 were non-CNS tumors), SFO was used in 11 patients (all of them being CNS tumors) and hybrid planswere used in 15 patients (including all 13 patients of CSI). Median number of fractions received was 30 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) for CNS patients to a median dose of 54CGE(40-55.8Gy) and 32 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) for non-CNS patients to a median dose of 59.4CGE (30.6-70.4). One patient of recurrent para-meningeal RMS received hyperfractionation with 52.8CGE in 40 fractions with a twice daily fractionation.…”
Section: Resultsmentioning
confidence: 99%
“…Xrays are commonly used, but in recent years there has been increasing availability and use of proton radiation, with the opening of new proton centres. Proton radiation has advantages over X-rays in its ability to spare exposure of normal brain tissue while maintaining equivalent antitumour efficacy [3,4]. This relative tissue sparing by protons is due to their differing physical interactions with matter.…”
Section: Introductionmentioning
confidence: 99%